Reaction of 1-(2-hydroxyphenyl)-3-phenylpropane-1, 3-dione with some phosphorus halides: A simple synthesis of novel 1, 2-benzoxaphosphinines. Issue 24 (17th December 2022) - Ali, Tarik E.; Assiri, Mohammed A.; Hassanin, Noha M.
Abstract: A simple method for design of some novel 1, 2-benzoxaphosphinines 2 –9, was achieved. The methodology depended on cyclization of 1-(2-hydroxy-phenyl)-3-phenylpropane-1, 3-dione (1 ) as starting material with some phosphorus halides in dry solvent in the presence of a base. Reaction of the substrate 1 with some phosphorus halides, such as P, P-dichlorophenylphosphine, phenyl phosphonic dichloride, phenyl phosphorodichloridate, and phosphorus oxychloride in dry toluene containing triethylamine led to a predominant formation of 3-benzoyl-4-hydroxy-2 H -1, 2-benzoxaphosphinines 2 –5, respectively. Under the same reaction conditions, the molecular structures of type 3-benzoyl-4 H -1, 2-benzoxaphosphinin-4-ones 6 and 7 were isolated by treatment of the substrate 1 with phosphorus pentachloride and phosphorus tribromide, respectively. In addition, the interesting 4-(1-phenyl-ethanoyl)-1, 2, λ 5 -benzoxaphosphinines 8 and 9 were obtained by treatment of compound 1 with acetonyl and benzyl triphenylphosphonium chlorides, respectively, in dry dioxane and sodium hydride. The chemical structures of the title compounds were established by elemental analysis and spectral tools. Graphical Abstract: UF0001